Initial study for early diagnosis of developmental problems: Relevant variables in the use of smart toys and resources - Laorden Gutiérrez, Cristina; Royo García, Pilar; Serrano García, Cristina; Núñez Nagy, Susana (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This study aims to contribute to the creation of smart, everyday toys that help in the early detection of developmental disorders in children. Three different monitored instruments (tower of cubes, peg board, digital tablet) have been used in order to identify the most relevant variables. The sample is formed by 144 children between the ages of 4 and 5. The results show that the most important variables are: the pressure applied when drawing in the digital tablet, the time spent on the pegboard task, and the acceleration and the shaking level in the building of the tower.